PREPARING A PRESCHOOL CHILD FOR SCHOOL EDUCATION BASED ON PSYCHOLOGICAL APPROACHES (Web of Teachers: Inderscience Research, 2024)
This article explores the psychological approaches to preparing preschool children for school education. It discusses the significance of early childhood development, the role of psychological readiness, and the application of modern methodologies in fostering cognitive, emotional, and social competencies in young learners. The article emphasizes the need for a balanced approach that aligns the developmental needs of children with the expectations of formal schooling, ensuring a smoother transition and a positive learning experience